Packaging and accelerated shelf life testing of ube powder (Dioscorea alata Linn.) - Toh, Maria Dulce Santamaria
The main objective of the study was to establish an equation for the ube powder through Accelerated Shelf Life Testing (ASLT) principles sing the Arrhenius relationship such that the parameters-moisture content and microbial count-will be expressed mathematically as rate equations. From the sorption data for ube powder obtained using the weight equilibrium method, a sigmoidal sorption isotherm was constructed. The monolayer value was calculated as 6.22. Experimental data on moisture content and microbial load were determined and equations representing the changes in moisture and microflora of the ube powder packed in different packaging materials and stored at different temperatures were derived. For moisture, storage at 0°C and 37°C, in PET/Al/PE was determined to accumulate the least level of moisture. At 55°C, PP was chosen as the most appropriate packaging material. In terms of microbial load of the product, storage at 0°C and 37°C using PET/Al/PE was determined to be significantly acceptable. At 55°C, CPP/VMOPP was determined significantly acceptable for the microbial integrity of ube powder. In ASLT using the Arrhenius relationship, both zero-order and first-order reactions were employed for moisture content. For both n=0 and n=1 of PP and CPP/VMOPP, the lowest moisure content curve was established at 55°C. For both n=0 and n=1 of PET/Al/PE, the product exposed at 37°C obtained the lowest moisture level curve. The difference between the order of reactions was the establishment of the respective curves. However, for microbial count, a first-order reaction was used in establishing the curves for each packaging material. The curve for ube powder packed in PP at 55°C, CPP/VMOPP at 0°C and PET/Al/PE at 37°C obtained an increasing curve for microbial load. In using the Q10 method, a plot was established through the use of shelf life estimates at a reference temperature of acceptability. Therefore, the two methods could be used in predicting the established parameters-moisture content and microbial count-of the ube powder. Limitations for each methods should be taken into account to minimize large deviations of the results.